Metaphysics of Presence and Difference: A Comparison of the Belief Systems Inherent in the Methodologies of Arts Based Research and A/r/tography - Haggarty, Holly Tsun (Journal of the Canadian Association for Curriculum Studies, 2020)
Arts-integrating approaches to research are increasingly engaged in the field of education. Arts-integrating approaches offer exciting opportunities for engaging creativity and imagination in research. However, researchers should be aware that the field of arts-integrating research encompasses a number of distinct methodologies, which entail varying understandings of what constitutes knowledge. From my (arts-integrating and phenomenological) comparative inquiry into two research methodologies, arts based research and a/r/tography, I conclude that they differ in their conceptions of knowledge, and that this difference is underpinned by differing beliefs regarding the nature of reality and being. Arts based research, as elaborated by Elliot Eisner and colleague Tom Barone (Barone & Eisner, 2006; Eisner, 1991) aligns with what may be called a metaphysics of presence, while a/r/tography, as elaborated by Rita Irwin and colleagues (Irwin & de Cossan, 2004; Springgay et al., 2008) espouses what may be called a metaphysics of difference. My inquiry parses the essential elements of these contrasting belief systems through two categories that I term primacy and unity. My findings provide a useful reflection on the unavoidably paradigmatic nature of all research.